Primary Squamous Cell Carcinoma of Thyroid: A case Report - Devkota, Ishwor Raj; Shrestha, Dipendra; Khadka, Subash (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Background: The thyroid gland lacks the squamous cell and the primary squamous cell carcinoma (SCC) of the thyroid gland is an uncommon malignancy with less than 1 % of all thyroid malignancy with a very poor prognosis. So far few cases are reported in the literature with very low survival rates. Case report: A 60 years female presented with a rapidly enlarging right lobe of the thyroid with pain, dysphagia and hoarseness of two months duration. She had hard fixed 4cm x 4cm right lobe of thyroid with right vocal cord paralysis. Ultrasound demonstrates 36mm x 36mm right lobe with mixed echogenicity with calcifications. Fine needle aspiration cytology suggested anaplastic carcinoma. Computed tomography showed heterogeneously enhancing soft tissue density in the right lobe of the thyroid gland measuring 51mm x 37mm x 53mm with shifting of the trachea towards the left side with no significant cervical lymph nodes. CT chest, ultrasonography abdomen and pelvis did not reveal any primary lesion or other metastatic disease and stage was made as T4N0M0. Patient underwent total thyroidectomy with center neck clearance with temporary tracheostomy. Histopathology came out to be squamous cell carcinoma and patient was send for chemo-radiotherapy. Conclusion: Primary squamous cell carcinoma of thyroid is a rare and aggressive entity with poor prognosis. Fine needle aspiration cytology is effective confirmatory tool but efforts shall be made to rule out metastatic SCC originating from other sites. Surgery, radiotherapy and chemotherapy alone are ineffective. Aggressive treatment with surgery followed by adjuvant radiotherapy with or without chemotherapy is recommended to achieve better outcome. Nepalese Journal of ENT Head and Neck Surgery, Vol. 6, No. 1, 2015